Characterizing the Toxicity of the Brazilian Extremist Communities on Telegram - Cavalini, Athus; Donadia, Thamya; Comarela, Giovanni (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2024.243207, 2024)
Telegram has become a central element in discussions related to the ecosystems of information disorder and extremism on social networks. Present on 70% of smartphones in Brazil, the application presents itself as a safe communication space, which began to be used by deplatformed individuals and groups, including extremist groups, who saw the application as a space for building communities and maintaining contact with their audience. In this context, this study presents a characterization of Brazilian extremist communities on Telegram based on the analysis of over 2 million messages broadcast on 128 chats on the platform, focusing on the analysis of the toxicity observed in the content shared in these spaces and its relationship with the conversational dynamics of the groups. The results reveal that these communities share highly toxic messages, including manifestations of hate speech and conspiracy theories, and that the toxicity of the content reflects on its popularity and consequently its spread across the network.